Penerapan Metode Pembelajaran Small Group Discussion untuk Meningkatkan Hasil Belajar dan Keaktifan Mahasiswa - Putriawati, Wiwin (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2019)
The Implementation of Small Group Discussion Learning Methods to Improve Learning Outcomes and Student Activity. This study aims to improve the learning outcomes and activeness of STKIP Paracendekia NW English Language Education students in the Basic Natural Sciences (IAD) course through the application of small group discussion methods. Student cognitive learning outcomes are still low, so it is necessary to apply new methods in learning. The activity in this research includes activeness in asking questions, answering questions, discussing, and presenting. This research is a classroom action research with two cycles. Stages of research include planning, implementation, observation, and reflection. The subjects of this study were 55 students of STKIP Paracendekia NW Sumbawa English Language Education semester I (one) in the Basic Science (IAD) course. Data collection techniques are tests (pretest and post test) and non-tests (observation). The result of this study were an increase in student learning outcomes and activity. Learning outcomes can be seen from the value of the pretest and post test. The average value of pretest and post test in cycle I is 65,22 and 70,67. Cycle II, the average value of the post test is 85,34. Student activeness before the action in only 15 active students. After being given the action, in the first cycle, students were activein asking, answering questions, discussing, and presenting 30 peoples. In cycle II, active students reached 42 peoples.